2007
DOI: 10.1111/j.1600-0420.2007.00934.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of dry eye related to systemic diseases in childhood and longterm follow‐up

Abstract: ABSTRACT.Purpose: Dry eye in children is not common in general practice and is usually referred to tertiary centres for diagnostic confirmation. In the present review we examine the potential causes of dry eye in children and report the management and longterm follow-up of dry eye in childhood with reference to clinical diversity, systemic associations, ocular outcomes and treatment trends. Methods: A retrospective, consecutive case series was studied by evaluating the clinical charts of children with dry eye … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 23 publications
(29 reference statements)
0
18
0
Order By: Relevance
“…Dry eye severe enough to cause ocular surface damage in children is rare, with little evidence available for treatment strategies 2 6 7…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 3 more Smart Citations
“…Dry eye severe enough to cause ocular surface damage in children is rare, with little evidence available for treatment strategies 2 6 7…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…In fact, in some of the children it was the ophthalmic examination that prompted a systemic evaluation and lead to the underlying diagnosis. In one other published report of dry eye in children, all 14 children had a concurrent systemic disease 2. It is advisable, therefore, for a child presenting with persisting signs or symptoms of dry eye syndrome to have a full paediatric history and clinical examination, so as to reveal or exclude a concurrent systemic condition.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…We are not aware of other studies that have reported the incidence of subjective complaints among SCT children. On the contrary, it has been suggested that DES questionnaires are less effective in paediatric patients (Mac Cord Medina et al 2007). …”
Section: Discussion Dry Eyesmentioning
confidence: 99%